Android-Based Tourism Geographic Information System For Blitar Raya Utilizing Google Maps API and Kotlin - Dimas Adi Pratama; Indyah Hartami Santi; Filda Febrinita (Jurnal Ilmiah Sistem Informasi, 2026)
The limited availability of integrated digital tourism information in Blitar Raya has made it challenging for visitors to plan their travel routes efficiently. This research aims to develop an Android-based Geographic Information System (GIS) that integrates the Google Maps API with the Bellman-Ford algorithm to optimize the shortest travel routes among tourism destinations. The system was developed using the Rapid Application Development (RAD) methodology, emphasizing user involvement through iterative prototyping and feedback. Primary data were collected from field observations, semi-structured interviews with tourists and local administrators, and beta testing involving 52 respondents, while secondary data were obtained from the Blitar Tourism Board and BPS statistical databases. The implementation integrates the Google Distance Matrix API to construct a weighted graph, which is processed by the Bellman-Ford algorithm, demonstrating higher route stability and accuracy than the Dijkstra and Haversine approaches in small-to-medium graph structures. The system achieved an 84.46% user acceptance rate, categorized as “Excellent” according to the ISO/IEC 25010 usability standard. Empirical findings show that the average response time of 1.5–2.5 seconds indicates high computational efficiency for real-time map rendering. This study contributes theoretically by presenting an algorithmic integration framework for mobile GIS applications and practically by offering a functional digital tourism platform to enhance local tourism management. The findings also suggest that combining RAD with algorithmic optimization can effectively bridge the gap between user experience and computational performance in tourism-based GIS systems.